Komodifikasi Perempuan: Tapak Ekonomi Neoliberal - Alia Swastika (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2003)
Economic advancement offered on the name of women emancipation turned to be tricky. On the one hand it allows women to leave its marginal posisition, yet the progress leave the women with dehumanization as neoliberal treat them as commodity. The prospect for woman participation in economy is rest on the ideological strength revived by fenimism.